3-min All-out Exercise Test for Running - Pettitt, R. W.; Jamnick, N.; Clark, I. E. (International Journal of Sports Medicine, 2012)
A 3-min all-out exercise test (3 MT) estimates critical power and the curvature constant for cycle ergometry validly; however, the mode of running has not been studied. We examined the efficacy of a running 3 MT, using global positioning sensor data, to predict outdoor racing performance. Women distance runners (n=14) were tested at preseason within a month prior to competing officially in either short or middle distance races. Critical speed (CS) (4.46±0.41 m/s) estimated from the 3 MT did not differ (p>0.05) from the mean speed of gas exchange threshold and maximum oxygen uptake (50%Δ), as derived from a custom treadmill graded exercise test (4.55±0.24 m/s). Runners with higher curvature constants (D’), estimated from the 3 MT, raced at higher speeds above CS (R2 ranging 0.63–0.99). Race speeds for 800 m exceeded the speed for 150 s of all-out running, rendering 800 m estimates less accurate. Conversely, predicted times for the other distances yielded strong intraclass correlations (α) and low coefficients of variation (%) values (α=0.74/1.7% and α=0.87/2.1%, for 1 600 and 5 000 m, respectively). Use of the running 3 MT for performances ranging ~2.5–18 min is recommended.
Keywords: anaerobic capacity; critical power; critical velocity; maximal steady state; VO2max